Persistent Genital Arousal Disorder: Confluent Patient History of Agitated Depression, Paroxetine Cessation, and a Tarlov Cyst. (26th November 2014) - Eibye, Simone; Jensen, Hans Mørch
Abstract : We report a case of a woman suffering from persistent genital arousal disorder (PGAD) after paroxetine cessation. She was admitted to a psychiatric department and diagnosed with agitated depression. Physical investigation showed no gynaecological or neurological explanation; however, a pelvic MRI scan revealed a Tarlov cyst. Size and placement of the cyst could not explain the patient's symptoms; thus neurosurgical approach would not be helpful. Her depression was treated with antidepressant with little effect. Electroconvulsive therapy improved the patient's symptoms though they did not fully resolve. More awareness of PGAD and thorough interdisciplinary conferences are necessary to insure an unequivocal treatment strategy.